1971
DOI: 10.1126/science.172.3979.169
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptides from the Surface of Control and Virus-Transformed Cells

Abstract: Glycopeptides were removed by trypsin digestion from the surface of control cells and cells transformed by Rous sarcoma virus, murine sarcoma virus, or polyoma virus. After digestion with pronase, the glycopeptides were analyzed by gel filtration. The elution profiles suggest that there are differences in the glycopeptides from the surface of control cells and those from transformed cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(56 citation statements)
references
References 8 publications
1
55
0
Order By: Relevance
“…This exon-intron structure is highly conserved in the mouse. 3 A similar genomic organization has been observed for the human ␤-1,4-GalT VI gene (31), which was also suggested by the similarity between human ␤-1,4-GalTs V and VI at the amino acid levels (32) and by a closer position of human ␤-1,4-GalT VI to that of human ␤-1,4-GalT V rather to other ␤-1,4-GalTs in the phylogenetic tree (33).…”
Section: Decreased Galactosylation Of Highly Branched N-glycans Bymentioning
confidence: 99%
See 2 more Smart Citations
“…This exon-intron structure is highly conserved in the mouse. 3 A similar genomic organization has been observed for the human ␤-1,4-GalT VI gene (31), which was also suggested by the similarity between human ␤-1,4-GalTs V and VI at the amino acid levels (32) and by a closer position of human ␤-1,4-GalT VI to that of human ␤-1,4-GalT V rather to other ␤-1,4-GalTs in the phylogenetic tree (33).…”
Section: Decreased Galactosylation Of Highly Branched N-glycans Bymentioning
confidence: 99%
“…The luciferase assay showed that the ␤-1,4-GalT V gene promoter is activated mostly in SH-SY5Y cells among the 2 T. Sato and K. Furukawa, unpublished data. 3 S. Hayakawa, T. Sato, and K. Furukawa, unpublished data. cell lines examined (Fig.…”
Section: Decreased Galactosylation Of Highly Branched N-glycans Bymentioning
confidence: 99%
See 1 more Smart Citation
“…A common alteration involves the increase in particular N-linked oligosaccharides when cells are transformed by a number of tumor viruses, including Rous sarcoma virus and polyoma virus, and oncogenes such as ras and fps/yes (Buck et al, 1971;Le Marer et al, 1992;Lu and Chaney, 1993;Pierce and Arango, 1986;Yamashita et al, 1984). These oligosaccharides contain a b(1,6) branched N-acetylglucosamine (GlcNAc) and their synthesis is catalyzed by the glycosyltransferase, N -acetylglucosaminyltransferase V (E. C. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Buck et al (1) reported this in 1970 for N-glycans from virus transformed cells. A number of immunologic epitopes identified as characteristic of malignant cells proved to be carbohydrate structures on lipids and proteins (2).…”
mentioning
confidence: 99%